Gut-immunity-joint axis: a new therapeutic target for gouty arthritis - Chen, Pei; Luo, Zhiqiang; Lu, Chengyin; Jian, Gonghui; Qi, Xinyu; Xiong, Hui (Frontiers in Pharmacology, 2024)
Gouty arthritis (GA) is an inflammatory disease characterized by pain. The primary goal of current treatment strategies during GA flares remains the reduction of inflammation and pain. Research suggests that the gut microbiota and microbial metabolites contribute to the modulation of the inflammatory mechanism associated with GA, particularly through their effect on macrophage polarization. The increasing understanding of the gut-joint axis emphasizes the importance of this interaction. The primary objective of this review is to summarize existing research on the gutimmune-joint axis in GA, aiming to enhance understanding of the intricate processes and pathogenic pathways associated with pain and inflammation in GA, as documented in the published literature.The refined comprehension of the gut-joint axis may potentially contribute to the future development of analgesic drugs targeting gut microbes for GA.